Developing a new aversive learning protocol in zebrafish (Danio rerio) - Jentze, Ada (2023)
The average age of humans is globally increasing, bringing along an increase of central nervous system disorders such as Alzheimer’s disease. Understanding the mechanisms and processes of learning and memory is therefore more important than ever. While widely studied in mammalian organisms, learning and memory are a relatively new study prospect for the teleost species zebrafish (Danio Rerio). Zebrafish is in many ways an ideal model organism: they have simple brain structures as well as well-known physiological and developmental properties in addition to being small, cheap, and easy to maintain. This study is the first step towards creating an easily accessible and replicable aversive learning protocol with minimal human interaction for further automation. On day one, the fish were conditioned with three short electric shocks at the end of a one-minute-long green LED-light (Paired group). The protocol was repeated three times during the conditioning day. The fish were tested for memory retention 24 hours after the last conditioning trial. The fish in the control group received either just the light (Light group) or just the shock (Shock group) during trials, and all fish received only the light during the test. The fish were filmed during the conditioning and testing and the videos were analyzed by using a movement tracking software. The fish in the Paired group increased movement in speed and distance during the memory retention testing due to the green light, which indicates learning. All groups however reacted to the green light, which can therefore not be considered as a neutral cue. Even though this protocol is a sufficient first step, the stimuli and the intervals between trials need to be further studied for replicable and reliable results. In the future the experimental setup should also be improved to better support automatization. Further tests on the fish, such as water cortisol level and brain monoamine quantity measurements could be conducted to gain a more holistic picture of the memory and learning processes.